THYMOMEGALY AND THE STATE OF HEALTH OF CHILDREN IN THE FIRST YEAR OF LIFE - Burkhanova D. S.; Tursunov F. O.; Musayeva F. (Galaxy International Interdisciplinary Research Journal, 2023)
This study shows the main reasons for the individual approach to the treatment and prevention program for children in their first years of life. At the same time, the features of thymomegaly in infancy in children are considered.